Unique nonclinical safety profile of PF-06835919, a ketohexokinase inhibitor, highlights a species-dependent mechanism - Jun Zhou; Christopher Houle; Frank J. Geoly; Sarah N. Campion; Jon Cook (Regulatory Toxicology and Pharmacology, 2026)

Thyroid dysregulation underlies altered ovarian cyclicity in rats exposed to PF-06835919, a ketohexokinase inhibitor - Sarah N. Campion; Christopher J. Bowman; Christopher Houle; Jessie Qian; Jun Zhou; Jon Cook (Reproductive Toxicology, 2026)

Conservation beyond protected areas: Understanding stakeholder perspectives on other effective area-based conservation measures - Alanna Marsh; Carly N. Cook (Ambio, 2026)
Other effective area-based conservation measures (OECMs) serve as an important tool to recognise diverse areas for their contributions to conservation, yet implementation remains slow. A key barrier to implementation is the lack of engagement with stakeholders who manage these areas and thus uncertainty about how best to secure their participation. We interviewed stakeholders representing different land uses that could be candidate OECMs in Australia, to capture their perspectives on OECMs and the factors that may motivate or deter their engagement. Stakeholder responses revealed an openness to and interest in OECMs, although many questions that are critical to their participation were raised. Concerns around long-term obligations and conflict between different management objectives were recurrent limitations to engagement. The opportunity for wider recognition of conservation efforts and increased social licence were key motivating factors. Important differences between stakeholder groups indicate that tailored strategies may improve engagement, which is a critical step in progressing OECMs.

Identifying hurricane and sea-level rise signatures in coastal oak forests of the Northeastern United States using a multi-parameter approach - N.K. Davi; L. Andreu-Hayles; C. Leland; A. Pacheco-Solana; M.P. Rao; E.R. Cook; N. Pederson (Global and Planetary Change, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Influences of subtle NMDA receptor blockade and allosteric modulation of α5 GABAA receptors on reward-related impulsivity in rats - Jovana Aranđelović; Bojan Batinić; Dishary Sharmin; Danijela Milenković; Đorđe Đorović; V. V. N. Phani Babu Tiruveedhula; James M Cook; Miroslav M Savić (Psychopharmacology, 2026)

Australian stingless bees exhibit greater sensitivity to dimethoate than Apis mellifera: implications for pesticide risk assessment - Gaurav Singh; James C. Makinson; Mary Finlay Doney; Onyeka Peter Nzie; James M. Cook; Robert N. Spooner-Hart (Pesticide Biochemistry and Physiology, 2026)

American oak imports to Britain and Ireland in the 18th and early 19th centuries; The dendrochronological evidence - A. Crone; A. Arnold; R. Bale; M. Bridge; D. Brown; E. Cook; C. Griggs; R. Howard; D. Miles; C. Mills; N. Nayling; C. Tyers; et al. (Dendrochronologia, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Lessons learned from screening potential other effective area‐based conservation measures - Carly N. Cook; Madhu Rao; Peter J. Clyne; Vanessa Rathbone; Christian Barrientos; Antonio Boveda; Alex Diment; Jorge Parra; Valeria Falabella; Matthew Linke; Deo Kujirakwinja; Stephane Ostrowski; et al. (Conservation Biology, 2026)
Other effective area‐based conservation measures (OECMs) are sites that deliver effective biodiversity outcomes irrespective of their management objectives. These areas are widely expected to play an important role in efforts to protect 30% of Earth by 2030. Despite general guidance to support screening sites against the formal criteria to be OECMs, progress recognizing sites has been limited. To advance the ability to identify OECMs, we developed a questionnaire that translates the components of the broad formal guidance into statements that experts can use to screen potential OECMs. Twenty‐eight local experts used the questionnaire to evaluate a large global sample of 81 sites. Most sites evaluated were largely in good condition and had the potential to achieve conservation outcomes, but none met the criteria to be considered OECMs. The most common challenges are related to threat management, adequate resourcing, and the ability to demonstrate that governance and management are achieving effective and sustained conservation outcomes. Based on the formal International Union for Conservation of Nature guidance, sites that only partially meet the relevant criteria remain candidate OECMs. Our questionnaire provides a nuanced way to assess OECMs that can help identify what support sites need to meet the necessary criteria. With effective long‐term conservation outcomes unable to be demonstrated for so many important conservation areas, our findings raise important questions about how to ensure area‐based conservation promotes positive and sustained outcomes for biodiversity.

Investigating the effects of biogenic amines on the dominance hierarchy in the small carpenter bee, Ceratina calcarata - Riya N. Miller; Sandra M. Rehan; Chelsea N. Cook; Colin S. Brent; Sarah P. Lawson (Insectes Sociaux, 2026)
Biogenic amines are highly conserved across animal species and aid in the regulation of movement, behavior, motivation, temperature, blood pressure, and endocrine secretion. Within eusocial species, such as the honey bee Apis mellifera , biogenic amines are responsible for modulating traits associated with higher levels of sociality, such as division of labor. In Ceratina calcarata , a facultatively social bee species, mothers establish a dominance hierarchy over their eldest daughter by providing them with less pollen and less protein, resulting in smaller, more submissive adults referred to as dwarf eldest daughters (DEDs). We hypothesized that this dominance hierarchy is additionally modulated by biogenic amines. To examine this hypothesis, we first compared biogenic amine levels between mothers and daughters and found significantly higher levels of dopamine, octopamine and tyramine in the mothers. To quantify the effects of these biogenic amine differences, dopamine was topically administered to C. calcarata DEDs, while the mothers were topically treated with the dopamine blocker cis-(Z)-Flupentixol dihydrochloride. Aggression helps to establish social hierarchies, so mothers and DEDs from the same nest underwent behavioral assays to assess aggressive and tolerant behaviors. When dopamine was blocked in the naturally more aggressive mothers, there was no difference in the number of aggressive interactions. Instead, treated mothers became more tolerant of DEDs, indicating dopamine plays a key role in modulating these behaviors. More work is needed to understand the different roles each biogenic amine plays in the development of a dominance hierarchy, especially in these species on the brink of eusociality.

The enemy of my enemy is not always my friend: Susceptibility of honey bee to entomopathogenic nematodes - Alihan Katlav; Sitaram Aryal; Manoj Dhakal; Michael Duncan; Clarissa M. House; Uffe N. Nielsen; James M. Cook; Robert N. Spooner-Hart; Markus Riegler (Journal of Invertebrate Pathology, 2026)

Multistage mineralisation in the Raja orogenic Au-Co prospect, Peräpohja belt, Finland: constraints from S isotopes and trace elements in pyrite, pyrrhotite and chalcopyrite - J. Tepsell; Y. Lahaye; F. Molnár; O. T. Rämö; N. Cook (Mineralium Deposita, 2026)
This study applies a multi-proxy geochemical approach to the Raja Au-Co prospect in northern Finland integrating trace element, S isotope, and textural data on sulphides and assessing these data against previously reported Ni, Cu and Fe isotope data. The combined dataset offers a more nuanced understanding of fluid evolution and mineralisation processes at Raja, classified as orogenic gold with atypical metal association. Our results support a multistage process, beginning with Co-only mineralisation driven by high-temperature, Co-rich metamorphic fluids, possibly from the evaporite-bearing Petäjäskoski formation, followed by a later hydrothermal overprint enriching Au. Early Co-rich fluids deposited euhedral pyrite (type A) with δ 34 S median of + 2.7‰, high Co/Ni ratio, and enrichment in Co, As, Se, Te, Bi, and Au. Subsequent metamorphism resulted in partial desulphidation of pyrite A, liberating Au, Co, and other trace elements and forming massive pyrrhotite, chalcopyrite, cobaltite, and Au-Bi-Te phases. Late-stage, Au-enriched fluids overprinted parts of the earlier Co-only mineralisation and deposited pyrite (type C) with δ 34 S median of + 5.6‰. Pyrite B, found in barren rocks, is unrelated to the mineralisation. Isotope and compositional variations in pyrite C suggest fluid mixing or pulsed activity involving magmatic-hydrothermal fluids and sedimentary-derived S. Our findings show that orogenic gold deposits with atypical metal association may form when Au-rich fluids overprint pre-existing base metal systems. This study illustrates how multivariate isotope geochemical methods can refine genetic models and unravel fluid evolution in epigenetic hydrothermal Au mineralisation in metamorphic belts, with implications for similar deposits in northern Finland and beyond.

Collaborative evaluation of in silico predictions for high throughput toxicokinetics - John F. Wambaugh; Nisha S. Sipes; Gilberto Padilla Mercado; Jon A. Arnot; Linda Bertato; Trevor N. Brown; Nicola Chirico; Christopher Cook; Daniel E. Dawson; Sarah E. Davidson-Fritz; Stephen S. Ferguson; Michael-Rock Goldsmith; et al. (Toxicology in Vitro, 2026)

An Expansion of Weight Inclusivity to Include Body Autonomy and Harm Reduction: Striving for Health Equity - Rachel W. Goode; Tyisha Harper-Cooks; Ana Paola Campos; Katherine Matthes; Julian Robles; Claudia M. Calderon; Michelle Chen Lee; Millicent N. Robinson; Ramine C. Alexander (Journal of the Academy of Nutrition and Dietetics, 2026)

Associations of endocrine disrupting chemical biomarkers and their mixture with vitamin D biomarker concentrations in childhood: The HOME Study - Katherine M. Marquess; Jordan R. Kuiper; Taylor M. Etzel; Bruce P. Lanphear; Andrew N. Hoofnagle; Antonia M. Calafat; Julianne Cook Botelho; Maria Ospina; Andreas Sjodin; Lesliam Quirós-Alcalá; Kim M. Cecil; Aimin Chen; et al. (Environmental Research, 2026)

Multi-temporal DEMs used to quantify the geomorphological impact of a late 20th century glacier re-advance at Schwarzberggletscher, Switzerland - Toby N. Tonkin; Nicholas G. Midgley; Simon J. Cook (Geomorphology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Tropical Biome Switching: Ant Communities Transition From Savanna to Rainforest Following Cessation of Burning - François Brassard; Kinjia Munkara‐Murray; Keith Cook; David Fell; Alan N. Andersen (Journal of Biogeography, 2025)
Savannas and rainforests co‐occur as mosaics across large areas of the tropics. These mosaics are dynamic, with savanna and rainforest switching in relatively short time scales, largely through the effects of fire. Most research to date addresses such biome switching through the lens of vegetation, with little attention given to faunal responses to transitions between savannas and rainforests. Aim To assess the responses of ant communities to biome switching from savanna to rainforest following 50 years of fire cessation. Location Iron Range (Kutini‐Payamu) on Australia's Cape York Peninsula. Taxon Subterranean, leaf litter, epigaeic, and arboreal ant assemblages. Methods We sampled ant assemblages using pitfall, subterranean and arboreal traps and leaf litter extractions across different vegetation types: savanna, secondary forest, primary dry forest and primary wet forest. Results The ant fauna was highly stratified, with distinct subterranean, leaf‐litter, epigaeic and arboreal assemblages. Ant communities in secondary forest were more similar to that in primary forest than in savanna. However, the secondary forest is still missing a range of specialist forest taxa, especially cryptobiotic species from the soil and leaf litter. The status of specialist canopy species remains unknown. Main Conclusions Despite low similarity in floristic composition due to a poor representation of primary rainforest trees in secondary forest, we find a clear switch from savanna to rainforest ant communities after 50 years of fire cessation. Even though full recovery of rainforest ant communities has not occurred, the current 50 year‐old secondary forest has much of the ant biodiversity value of primary rainforest, including for regionally endemic species that are rainforest specialists. This provides further evidence that ant communities respond more strongly to vegetation structure than to floristic composition.

Rhenium-osmium and oxygen isotope homogeneity during the 2022 Mauna Loa eruption and implications for basaltic magma storage - Emily A. Rhoads; Anton Kutyrev; Ilya N. Bindeman; Kendra J. Lynn; Frank A. Trusdell; Drew T. Downs; Hunter R. Edwards; Geoffrey W. Cook; James M. D. Day (Bulletin of Volcanology, 2025)
Mauna Loa is one of the largest and most active volcanoes on Earth. The most recent eruption of Mauna Loa started on 27 November 2022, lasted for 13 days, and was preceded by the longest repose time of 38 years in its modern history. In this contribution, new trace- and highly siderophile-element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances, 187 Re- 187 Os, and 18 O/ 16 O data are reported for the 2022 lavas. These lavas have a limited range of MgO (6.2 ± 0.1 wt.%) and Ni (83 ± 2 µg/g), with a broader range of Re (0.3 to 1.3 ng/g) and consistent Os (0.031 to 0.080 ng/g) contents. They have 187 Os/ 188 Os ratios (0.1345 to 0.1385) which are, on average, more radiogenic than Mauna Loa picrites (0.1331 to 0.1349) and are similar in composition to more differentiated Mauna Loa tholeiite lavas (0.1340 to 0.1381). The oxygen isotope compositions of glassy samples are 5.35 ± 0.15‰ ( n = 13) and span a range in δ 18 O of + 5.0 to + 5.5‰, with an average composition 0.2 to 0.3‰ lower than MORB. The δD value is − 81 ± 11‰ ( n = 5) at very low (0.03 ± 0.015 wt.%) H 2 O concentrations. The 2022 Mauna Loa eruption is similar in terms of δ 18 O but contrasts in terms of 187 Os/ 188 Os variability, with the recent longer-lived eruptions on La Palma (Canary Islands; 85 days) in 2021 and on the Reykjanes Peninsula (Iceland) that began in 2021 and are still ongoing. Initial lavas were more fractionated for both the Canary Islands and Iceland eruptions, producing more radiogenic Os isotope compositions than later erupted products. The 2022 Mauna Loa eruption showed no such trends. The limited range in isotope compositions of the 2022 Mauna Loa lavas and their strongly fractioned HSE patterns reflect long-term storage, crystal fractionation, and assimilation of related basaltic volcanic edifice materials by the parent magma beneath the volcano prior to eruption triggering. Eruption of differentiated and homogeneous tholeiite lavas at the summit caldera and high on the volcano’s flank, with emplacement of accumulative picrites lower on the volcano, are consistent with neutral buoyancy arguments.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Application of Ni, Cu and Fe isotopes as indicators of ore genesis - New insights from the epigenetic-hydrothermal Rajapalot Au Co prospect, Finnish Lapland - J. Tepsell; Y. Lahaye; F. Molnár; O.T. Rämö; N. Cook (Chemical Geology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Wild native insects are efficient pollinators of mangoes in the Northern Territory of Australia - Gaurav Singh; James C. Makinson; Amy M. Gilpin; Robert N. Spooner-Hart; James M. Cook (Agriculture, Ecosystems & Environment, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Remission cytochrome spectroscopy reveals the mode of action of bedaquiline in living mycobacteria - Suzanna H. Harrison; Rowan C. Walters; Morwan M. Osman; Roger J. Springett; Gregory M. Cook; James N. Blaza (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Per- and polyfluoroalkyl substances (PFAS), perceived stress, and depressive symptoms in a prospective cohort study of black women - Samantha Schildroth; Birgit Claus Henn; Anissa I. Vines; Ruth J. Geller; Sharonda M. Lovett; Chad M. Coleman; Traci N. Bethea; Julianne Cook Botelho; Antonia M. Calafat; Chad Milando; Donna D. Baird; Ganesa Wegienka; et al. (Science of The Total Environment, 2024)

Facultatively ectoparasitic mites as vectors for entomopathogenic bacteria in Drosophila - Emily K. Stone; Emily S. Durkin; Andrew Cook; Elise A. Richardson; Brian P. Lazzaro; Carl N. Keiser (Journal of Invertebrate Pathology, 2024)

Silver isotope analysis and systematics of native gold from the Rajapalot Co-enriched gold deposit, Finnish Lapland - J. Tepsell; Y. Lahaye; F. Molnár; O.T. Rämö; N. Cook (Mineralium Deposita, 2024)
Silver is probably the closest isotopic proxy to track monoisotopic gold and has been shown to have great potential to yield new information on the origin and enrichment processes of gold. This study describes the development of a tailored analytical protocol for accurate analysis of Ag isotopes and provides the first Ag isotope data for the Paleoproterozoic Rajapalot Au-Co deposit, Finnish Lapland. Six native Au samples yield ε 109 Ag values (relative to NIST SRM 978a) from −6.8 to +2.1 and are within the range of Ag isotopic compositions reported for native Au samples. The mean of the analyzed Au samples is ε 109 Ag = −3.8 ± 1.7 (2SD) with most of the samples with negative ε 109 Ag values (−6.7 to −2.0); one sample has a positive ε 109 Ag value of +2.1 ± 0.5. Silver isotope fractionation in the Rajapalot Au deposit was likely associated with physicochemical processes related to deposition and/or re-mobilization of the ore rather than with source region inheritance. It is suggested that redox reactions involving Ag + ↔ Ag 0 phase change primarily account for the isotopic differences within the deposit. Our results also suggest that the Rajapalot Au-Co deposit was formed via multistage ore-forming processes and/or that the primary ore was re-mobilized, which caused isotope fractionation along fluid pathways. Silver isotope variation within a deposit may mark a fractional crystallization trend with the lightest isotopic composition representing the earliest precipitate. Hence, Ag isotopes show potential as an isotopic vectoring tool in search of Au-enriched domains.

A tale of 3 dwarf planets: Ices and organics on Sedna, Gonggong, and Quaoar from JWST spectroscopy - J.P. Emery; I. Wong; R. Brunetto; J.C. Cook; N. Pinilla-Alonso; J.A. Stansberry; B.J. Holler; W.M. Grundy; S. Protopapa; A.C. Souza-Feliciano; E. Fernández-Valenzuela; J.I. Lunine; et al. (Icarus, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Deep learning of estuary salinity dynamics is physically accurate at a fraction of hydrodynamic model computational cost - Galen Gorski; Salme Cook; Amelia Snyder; Alison P. Appling; Theodore Thompson; Jared D. Smith; John C. Warner; Simon N. Topp (Limnology and Oceanography, 2024)
Salinity dynamics in the Delaware Bay estuary are a critical water quality concern as elevated salinity can damage infrastructure and threaten drinking water supplies. Current state‐of‐the‐art modeling approaches use hydrodynamic models, which can produce accurate results but are limited by significant computational costs. We developed a machine learning (ML) model to predict the 250 mg L −1 Cl − isochlor, also known as the “salt front,” using daily river discharge, meteorological drivers, and tidal water level data. We use the ML model to predict the location of the salt front, measured in river miles (RM) along the Delaware River, during the period 2001–2020, and we compare predictions of the ML model to the hydrodynamic Coupled Ocean–Atmosphere‐Wave‐Sediment Transport (COAWST) model. The ML model predicts the location of the salt front with greater accuracy (root mean squared error [RMSE] = 2.52 RM) than the COAWST model does (RMSE = 5.36); however, the ML model struggles to predict extreme events. Furthermore, we use functional performance and expected gradients, tools from information theory and explainable artificial intelligence, to show that the ML model learns physically realistic relationships between the salt front location and drivers (particularly discharge and tidal water level). These results demonstrate how an ML modeling approach can provide predictive and functional accuracy at a significantly reduced computational cost compared to process‐based models. In addition, these results provide support for using ML models in operational forecasting, scenario testing, management decisions, hindcasting, and resulting opportunities to understand past behavior and develop hypotheses.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Measurement of D/H and 13C/12C ratios in methane ice on Eris and Makemake: Evidence for internal activity - W.M. Grundy; I. Wong; C.R. Glein; S. Protopapa; B.J. Holler; J.C. Cook; J.A. Stansberry; J.I. Lunine; A.H. Parker; H.B. Hammel; S.N. Milam; R. Brunetto; et al. (Icarus, 2024)

Effects of establishment fertilization on Landsat-assessed leaf area development of loblolly pine stands - Matthew N. House; Randolph H. Wynne; Valerie A. Thomas; Rachel L. Cook; David R. Carter; Jennifer H. Van Mullekom; Jim Rakestraw; Todd A. Schroeder (Forest Ecology and Management, 2024)

Monitoring for the presence of invasive arboreal rodents: an assessment of monitoring tools across forest strata - Alexandra H. Nance; Melinda Wilson; Carly N. Cook; Rohan H. Clarke (Biological Invasions, 2024)

Species and ecological communities as management surrogates for threatened biodiversity - Javiera Olivares-Rojas; Carly N. Cook; Michelle S. Ward; Jessica C. Walsh (Biodiversity and Conservation, 2024)
In the face of the ongoing biodiversity crisis and limited conservation funding, surrogate approaches have become a valuable tool to represent biodiversity. Management surrogates are those that indirectly benefit an ecological system or species by representing the management requirements of co-occurring biodiversity. Recent findings highlight the cost-effective potential of surrogate species in managing threatened species, however, evaluating higher levels of biodiversity as management surrogates remains unexplored. Here, we sought to maximize conservation outcomes for threatened species and threatened ecological communities (TECs) by prioritizing management based on overlapping distributions, threats, and costs. We describe a prioritization framework for identifying TECs that could serve as cost-effective surrogates, and compare it with prioritizing threatened species only or both species and TECs. We show that when the objective is to maximize benefits for threatened species, a community approach performs poorly due to limited geographic overlap and high costs, while prioritizing species returned 7.5 times more benefits delivered to species under the same budget. Yet, if the objective is to maximize benefits across species and TECs simultaneously, a combined approach including both as surrogates delivers the greatest benefit for the same costs as a species-only approach. Range sizes and taxonomic groups significantly influenced the priority list, with threatened invertebrates and TECs of smaller ranges more likely to be selected as surrogates. Overall, this study emphasizes the importance of incorporating accurate data on factors such as threats and costs for identifying effective management surrogates, and highlights the potential benefits of prioritizing across multiple biodiversity features.

Progress developing the concept of other effective area‐based conservation measures - Carly N. Cook (Conservation Biology, 2024)
In 2010, the introduction of other effective area‐based conservation measures (OECMs) into international policy caused a paradigm shift in area‐based conservation, which included consideration of areas outside formal protected areas and places where biodiversity conservation may not be a management objective for the site. Despite the importance of this shift for global conservation, conservation science and policy have been slow to engage with the concept of OECMs. As the world moves toward protecting 30% of the Earth by 2030, it is imperative to develop evidence‐based guidance for how to identify effective conservation measures, especially tools to help evaluate and monitor the biodiversity outcomes associated with potential OECMs. To understand the current progress in developing the concept of OECMs, I evaluated the peer‐reviewed literature to consolidate and synthesize current knowledge. I conducted a thematic analysis of papers to identify the types of challenges and opportunities being discussed and lessons from studies evaluating the effectiveness of OECMs. Only 105 studies mentioned OECMs, and those that did rarely move beyond superficial mention of OECMs as part of area‐based conservation. Around one‐half of studies listed potential risks or benefits of OECMs but none provided evidence these issues have materialized. Twenty‐three studies attempted to identify potential OECMs, although specific case studies were rare. The 7 studies that evaluated existing OECMs were highly critical of how they had been implemented to date. Studies that evaluated conservation outcomes were extremely rare, and suggested effectiveness must be judged on a case‐by‐case basis. The current literature not only leaves many gaps in the science required to operationalize the concept of OECMs, but also often raises additional questions that need to be addressed. If these gaps are not filled by robust science, the promised benefits for biodiversity from OECMs may never be realized.

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Global variability and controls on the accumulation of fallout radionuclides in cryoconite - Caroline C. Clason; Giovanni Baccolo; Edyta Łokas; Philip N. Owens; Przemyslaw Wachniew; Geoff E. Millward; Alex Taylor; Will H. Blake; Dylan B. Beard; Ewa Poniecka; Nick Selmes; Elizabeth A. Bagshaw; et al. (Science of The Total Environment, 2023)

Heat stress survival and thermal tolerance of Australian stingless bees - Scott Nacko; Mark A. Hall; Rosalyn Gloag; Kate E. Lynch; Robert N. Spooner-Hart; James M. Cook; Markus Riegler (Journal of Thermal Biology, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

Pulses of labile carbon cause transient decoupling of fermentation and respiration in permeable sediments - Philipp A. Nauer; Adam J. Kessler; Puspitaningsih Hall; Maria Elena Popa; Sophie ten Hietbrink; Tess Hutchinson; Wei Wen Wong; Karl Attard; Ronnie N. Glud; Chris Greening; Perran L. M. Cook (Limnology and Oceanography, 2023)
Dihydrogen (H 2 ) is an important intermediate in anaerobic microbial processes, and concentrations are tightly controlled by thermodynamic limits of consumption and production. However, recent studies reported unusual H 2 accumulation in permeable marine sediments under anoxic conditions, suggesting decoupling of fermentation and sulfate reduction, the dominant respiratory process in anoxic permeable marine sediments. Yet, the extent, prevalence and potential triggers for such H 2 accumulation and decoupling remain unknown. We surveyed H 2 concentrations in situ at different settings of permeable sand and found that H 2 accumulation was only observed during a coral spawning event on the Great Barrier Reef. A flume experiment with organic matter addition to the water column showed a rapid accumulation of hydrogen within the sediment. Laboratory experiments were used to explore the effect of oxygen exposure, physical disturbance and organic matter inputs on H 2 accumulation. Oxygen exposure had little effect on H 2 accumulation in permeable sediments suggesting both fermenters and sulfate reducers survive and rapidly resume activity after exposure to oxygen. Mild physical disturbance mimicking sediment resuspension had little effect on H 2 accumulation; however, vigorous shaking led to a transient accumulation of H 2 and release of dissolved organic carbon suggesting mechanical disturbance and cell destruction led to organic matter release and transient decoupling of fermenters and sulfate reducers. In summary, the highly dynamic nature of permeable sediments and its microbial community allows for rapid but transient decoupling of fermentation and respiration after a C pulse, leading to high H 2 levels in the sediment.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

A prospective nested case-control study of serum concentrations of per- and polyfluoroalkyl substances and aggressive prostate cancer risk - Jongeun Rhee; Kathryn H. Barry; Wen-Yi Huang; Joshua N. Sampson; Jonathan N. Hofmann; Debra T. Silverman; Antonia M. Calafat; Julianne Cook Botelho; Kayoko Kato; Mark P. Purdue; Sonja I. Berndt (Environmental Research, 2023)

Foresight science in conservation: Tools, barriers, and mainstreaming opportunities - Gabrielle Ednie; Tyreen Kapoor; Olga Koppel; Morgan L. Piczak; Jessica L. Reid; Alyssa D. Murdoch; Carly N. Cook; William J. Sutherland; Steven J. Cooke (Ambio, 2023)

Analysis of Charon’s spectrum at 2.21- μ m from New Horizons/LEISA and Earth-based observations - Jason C. Cook; Silvia Protopapa; Cristina M. Dalle Ore; Dale P. Cruikshank; William M. Grundy; Carey M. Lisse; Bernard Schmitt; Anne Verbiscer; Kelsi N. Singer; John Spencer; S. Alan Stern; Harold A. Weaver (Icarus, 2023)

Mid- and long-chain leaf wax δ2H values in modern plants and lake sediments from mid-latitude North America - Ioana C. Stefanescu; Chandelle Macdonald; Craig S. Cook; David G. Williams; Bryan N. Shuman (Geochimica et Cosmochimica Acta, 2023)

Defining performance thresholds for effective management of biodiversity within protected areas - Mairi Hilton; Carly N. Cook (Conservation Biology, 2022)
Performance thresholds are an important tool for determining successful conservation outcomes. They provide an objective means of defining good ecological condition and have been endorsed as an essential part of best practice in protected area (PA) management within the International Union for the Conservation of Nature Green List of Protected and Conserved Areas Standard. With a growing number of PAs attaining Green List status globally, thresholds developed by PAs on the Green List present an excellent resource with which to identify the attributes of well‐defined performance thresholds. We examined 349 thresholds associated with PAs on the Green List to determine whether they were specific and measurable (i.e., factors recognized as essential for setting well‐defined targets). We assessed whether thresholds were defined quantitatively and whether definitions included ambiguous terms (e.g., stable numbers ). We identified six different ways thresholds were expressed and found that many thresholds were expressed as management objectives, rather than ecological condition thresholds, although this trend improved over time. Approximately one‐half of the performance thresholds lacked the necessary specificity to delineate successful outcomes. Our results enabled us to develop a checklist of information required to set robust performance thresholds. Recommendations include that thresholds should be quantitatively defined, including quantitative estimates of the limits of acceptable change (LAC) around the target condition. To ensure transparency, a rationale and associated evidence should be provided to support the threshold and the LAC. When accompanied by a rationale and quantitative estimate of the current condition of the value, unambiguously defined thresholds with a quantitative LAC provide an objective means of demonstrating that successful conservation outcomes have been achieved. These recommendations will help conservation managers apply the Green List Standard and improve the measurement of conservation outcomes more broadly.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Cooperative breeding and the emergence of multilevel societies in birds - Ettore Camerlenghi; Alexandra McQueen; Kaspar Delhey; Carly N. Cook; Sjouke A. Kingma; Damien R. Farine; Anne Peters (Ecology Letters, 2022)
Multilevel societies (MLSs), where social levels are hierarchically nested within each other, are considered one of the most complex forms of animal societies. Although thought to mainly occurs in mammals, it is suggested that MLSs could be under‐detected in birds. Here, we propose that the emergence of MLSs could be common in cooperatively breeding birds, as both systems are favoured by similar ecological and social drivers. We first investigate this proposition by systematically comparing evidence for multilevel social structure in cooperative and non‐cooperative birds in Australia and New Zealand, a global hotspot for cooperative breeding. We then analyse non‐breeding social networks of cooperatively breeding superb fairy‐wrens ( Malurus cyaneus ) to reveal their structured multilevel society, with three hierarchical social levels that are stable across years. Our results confirm recent predictions that MLSs are likely to be widespread in birds and suggest that these societies could be particularly common in cooperatively breeding birds.

Prioritization and thresholds for managing biological invasions in urban ecosystems - L. J. Potgieter; M. F. J. Aronson; A. J. Brandt; C. N. Cook; M. Gaertner; N. E. Mandrak; D. M. Richardson; N. Shrestha; M. W. Cadotte (Urban Ecosystems, 2022)

Lessons from other disciplines for setting management thresholds for biodiversity conservation - Mairi Hilton; Jessica C. Walsh; Erin Liddell; Carly N. Cook (Conservation Biology, 2022)
Successful, state‐dependent management, in which the goal of management is to maintain a system in a desired state, involves defining the boundaries between different states. Once these boundaries have been defined, managers require a strategic action plan with thresholds that initiate management interventions to either maintain or return the system to a desired state. This approach to management is widely used across diverse industries from agriculture, to medicine, to information technology, but it has only been adopted in conservation management relatively recently. Conservation practitioners have expressed a willingness to integrate this structured approach in their management systems, but they have also voiced concerns, including lack of a robust process for doing so. Given the widespread use of state‐dependent management in other fields, we conducted an extensive review of the literature on threshold‐based management to gain insight into how and where it is applied and identify potential lessons for conservation management. We identified 22 industries using 75 different methods for setting management thresholds in 843 studies. Methods spanned six broad approaches, including expert driven, statistical, predictive, optimization, experimental, and artificial intelligence methods. The objectives of each of these studies influenced the approaches used, including the methods for setting thresholds and selecting actions, and the number of thresholds set. The role of value judgments in setting thresholds was clear; studies across all industries frequently involved experts in setting thresholds, often accompanied by computational tools to simulate the consequences of proposed thresholds under different conditions. Of the 30 conservation studies examined, two‐thirds used expert‐driven methods, consistent with prior evidence that experience‐based information often drives conservation management decisions. The methods we identified from other disciplines could help conservation decision makers set thresholds for management interventions in different contexts, linking monitoring to management actions and ensuring that conservation interventions are timely and effective.

Geographic variation of mercury in breeding tidal marsh sparrows of the northeastern United States - Christopher J. Sayers; Mackenzie R. Roeder; Lindsay M. Forrette; Daniel Roche; Gaetan L. B. Dupont; Sam E. Apgar; Alison R. Kocek; Alexandra M. Cook; W. Gregory Shriver; Chris S. Elphick; Brian Olsen; David N. Bonter (Ecotoxicology, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Small artificial waterbodies are widespread and persistent emitters of methane and carbon dioxide - M. Peacock; J. Audet; D. Bastviken; S. Cook; C. D. Evans; A. Grinham; M. A. Holgerson; L. Högbom; A. E. Pickard; P. Zieliński; M. N. Futter (Global Change Biology, 2021)
Inland waters play an active role in the global carbon cycle and emit large volumes of the greenhouse gases (GHGs), methane (CH 4 ) and carbon dioxide (CO 2 ). A considerable body of research has improved emissions estimates from lakes, reservoirs and rivers but recent attention has been drawn to the importance of small, artificial waterbodies as poorly quantified but potentially important emission hotspots. Of particular interest are emissions from drainage ditches and constructed ponds. These waterbody types are prevalent in many landscapes and their cumulative surface areas can be substantial. Furthermore, GHG emissions from constructed waterbodies are anthropogenic in origin and form part of national emissions reporting, whereas emissions from natural waterbodies do not (according to Intergovernmental Panel on Climate Change guidelines). Here, we present GHG data from two complementary studies covering a range of land uses. In the first, we measured emissions from nine ponds and seven ditches over a full year. Annual emissions varied considerably: 0.1–44.3 g CH 4 m −2 year −1 and −36–4421 g CO 2 m −2 year −1 . In the second, we measured GHG concentrations in 96 ponds and 64 ditches across seven countries, covering subtropical, temperate and sub‐arctic biomes. When CH 4 emissions were converted to CO 2 equivalents, 93% of waterbodies were GHG sources. In both studies, GHGs were positively related to nutrient status (C, N, P), and pond GHG concentrations were highest in smallest waterbodies. Ditch and pond emissions were larger per unit area when compared to equivalent natural systems (streams, natural ponds). We show that GHG emissions from natural systems should not be used as proxies for those from artificial waterbodies, and that artificial waterbodies have the potential to make a substantial but largely unquantified contribution to emissions from the Agriculture, Forestry and Other Land Use sector, and the global carbon cycle.

Detection of Hepatitis A Virus in Strawberries Implicated in an Outbreak in the USA in 1997 - N. Cook; L. Vickers-Smith; M. D’Agostino (Food and Environmental Virology, 2021)

Understanding biosecurity: knowledge, attitudes and practices of seaweed farmers in the Philippines - Jonalyn P. Mateo; Iona Campbell; Elizabeth J. Cottier-Cook; Maria Rovilla J. Luhan; Victor Marco Emmanuel N. Ferriols; Anicia Q. Hurtado (Journal of Applied Phycology, 2021)
Farmers are one of the most important components of any plant-based cultivation industry. The Philippines is one of the world’s major producers of red carrageenophyte algae and has tens of thousands of farmers involved in this industry. The production of algae such as Kappaphycus and Eucheuma increased significantly from the early 1970s, when the industry was established, before declining from the mid-2000s, due to a number of reasons, including disease and epiphyte outbreaks. The introduction of biosecurity measures has been one approach used to tackle this decline. Biosecurity-related knowledge, attitude and practices (KAP) of the seaweed farmers were assessed in the four highest seaweed producing regions in the Philippines: (1) Tawi-Tawi, (2) Palawan, (3) Zamboanga and (4) Bohol. Analyses showed that seaweed farmers from Tawi-Tawi had relatively higher KAP mean scores than the other three sites. Palawan and Bohol farmers, however, scored lower on their knowledge, higher on their attitude and highest on their practices compared with the other areas. Farmers from Zamboanga scored the lowest in both their attitude and practice mean scores, although their knowledge score was one of the highest. This is the first KAP assessment applied to the seaweed farming industry globally and the results, in which the farmers’ biosecurity-related knowledge and practices, which scored “Fair” (50–75%) across all the regions, and their attitudes, which scored predominantly “Good” (> 75%) suggest that there is potential to raise the score for biosecurity practices. This assessment highlights how biosecurity challenges are currently addressed by seaweed farmers in the Philippines and suggests how the KAP survey could be used as a tool by policymakers and scientists to address gaps in biosecurity management practices.

Assessing the current state of ecological connectivity in a large marine protected area system - Kelsey E. Roberts; Carly N. Cook; Jutta Beher; Eric A. Treml (Conservation Biology, 2021)
The establishment of marine protected areas (MPAs) is a critical step in ensuring the continued persistence of marine biodiversity. Although the area protected in MPAs is growing, the movement of individuals (or larvae) among MPAs, termed connectivity, has only recently been included as an objective of many MPAs. As such, assessing connectivity is often neglected or oversimplified in the planning process. For promoting population persistence, it is important to ensure that protected areas in a system are functionally connected through dispersal or adult movement. We devised a multi‐species model of larval dispersal for the Australian marine environment to evaluate how much local scale connectivity is protected in MPAs and determine whether the extensive system of MPAs truly functions as a network. We focused on non‐migratory species with simplified larval behaviors (i.e., passive larval dispersal) (e.g., no explicit vertical migration) as an illustration. Of all the MPAs analyzed (approximately 2.7 million km 2 ), outside the Great Barrier Reef and Ningaloo Reef,

Characteristics of Transgender Patient Cases Managed by a Toxicologist: an Analysis of the Toxicology Investigator’s Consortium (ToxIC) Registry: January 2017–June 2019 - Ryan M. Surmaitis; Marna Rayl Greenberg; Natalie E. Ebeling-Koning; Phillip M. Grenz; Cody R. McWhirter; Beth A. Careyva; Judith N. Sabino; Matthew D. Cook; Robert D. Cannon; Andrew L. Koons; Kenneth D. Katz; Hope Kincaid; et al. (Journal of Medical Toxicology, 2021)

Early olfactory, but not gustatory processing, is affected by the selection of heritable cognitive phenotypes in honey bee - Meghan M. Bennett; Chelsea N. Cook; Brian H. Smith; Hong Lei (Journal of Comparative Physiology A, 2021)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Racial and ethnic differences in risk of second primary cancers among prostate cancer survivors - Diana R. Withrow; Sara J. Schonfeld; Rochelle E. Curtis; Lindsay M. Morton; Michael B. Cook; Eboneé N. Butler; Amy Berrington de González (Cancer Causes & Control, 2020)

Low‐coverage genomic data resolve the population divergence and gene flow history of an Australian rain forest fig wasp - Lisa Cooper; Lynsey Bunnefeld; Jack Hearn; James M. Cook; Konrad Lohse; Graham N. Stone (Molecular Ecology, 2020)
Population divergence and gene flow are key processes in evolution and ecology. Model‐based analysis of genome‐wide data sets allows discrimination between alternative scenarios for these processes even in nonmodel taxa. We used two complementary approaches (one based on the blockwise site frequency spectrum [bSFS], the second on the pairwise sequentially Markovian coalescent [PSMC]) to infer the divergence history of a fig wasp, Pleistodontes nigriventris . Pleistodontes nigriventris and its fig tree mutualist Ficus watkinsiana are restricted to rain forest patches along the eastern coast of Australia and are separated into The Northern population is to the north of the Southern populations by two dry forest corridors (the Burdekin and St. Lawrence Gaps). We generated whole genome sequence data for two haploid males per population and used the bSFS approach to infer the timing of divergence between northern and southern populations of P. nigriventris , and to discriminate between alternative isolation with migration (IM) and instantaneous admixture (ADM) models of postdivergence gene flow. Pleistodontes nigriventris has low genetic diversity (π = 0.0008), to our knowledge one of the lowest estimates reported for a sexually reproducing arthropod. We find strongest support for an ADM model in which the two populations diverged ca . 196 kya in the late Pleistocene, with almost 25% of northern lineages introduced from the south during an admixture event ca. 57 kya. This divergence history is highly concordant with individual population demographies inferred from each pair of haploid males using PSMC. Our analysis illustrates the inferences possible with genome‐level data for small population samples of tiny, nonmodel organisms and adds to a growing body of knowledge on the population structure of Australian rain forest taxa.

Tackling the tide: A rapid assessment protocol to detect terrestrial vertebrates in mangrove forests - Stefanie M. Rog; Rohan H. Clarke; Ernest Minnema; Carly N. Cook (Biodiversity and Conservation, 2020)

Simulating alternative sustainable water futures - D. A. Sampson; E. M. Cook; M. J. Davidson; N. B. Grimm; D. M. Iwaniec (Sustainability Science, 2020)

Analysis of biosecurity-related policies governing the seaweed industry of the Philippines - Jonalyn P. Mateo; Iona Campbell; Elizabeth J. Cottier-Cook; Maria Rovilla J. Luhan; Victor Marco Emmanuel N. Ferriols; Anicia Q. Hurtado (Journal of Applied Phycology, 2020)

Ultra-endurance triathlon performance and markers of whole-body and gut-specific inflammation - Kyle A. Smith; Jacob N. Kisiolek; Brandon D. Willingham; Margaret C. Morrissey; Samantha M. Leyh; Patrick G. Saracino; Daniel A. Baur; Marc D. Cook; Michael J. Ormsbee (European Journal of Applied Physiology, 2020)

The case for embedding researchers in conservation agencies - Dirk J. Roux; Richard T. Kingsford; Carly N. Cook; Jane Carruthers; Katrina Dickson; Marc Hockings (Conservation Biology, 2019)
Although protected areas represent a pivotal response to escalating anthropogenic threats, they face many pressures, inside and outside their boundaries. Amid these challenges, effective conservation is guided by evidence‐based decision making supported by dynamic processes of learning and knowledge exchange. Although different models promote knowledge exchange, embedding research scientists within conservation agencies is best suited to supporting evidence‐based conservation. Based on available literature and our experiences on several continents, we considered the benefits, challenges, and opportunities associated with embedding research scientists within conservation agencies and the research required to better understand the effectiveness of the embedding model for evidence‐based conservation. Embedded researchers provide long‐term commitment to building social capital among academic and nonacademic stakeholders; act as skilled gatekeepers who increase 2‐way flow of knowledge between scientists and managers; attract, coordinate, and support management‐relevant external research projects; drive the design and maintenance of long‐term monitoring; and align their research with information needs. Notwithstanding the many benefits, research capacity of conservation agencies is declining worldwide. A significant challenge is that the values, structures, functions, and effectiveness of the embedding model of knowledge exchange remain poorly evaluated and documented. Also, embedded researchers have to balance their desire for creativity and flexibility with the standardization and quality control required by their public sector agencies; may be perceived as not credible because they are not truly independent of their agency; and have to couple scientific productivity with skills for transdisciplinary research, social facilitation, and stakeholder engagement. Systematic research on embedding and other models of knowledge exchange, across different world contexts, is required to better understand the benefits, costs, and institutional arrangements associated with different models.

Spiraling Down Hillslopes: Nutrient Uptake from Water Tracks in a Warming Arctic - Tamara K. Harms; Christopher L. Cook; Adam N. Wlostowski; Michael N. Gooseff; Sarah E. Godsey (Ecosystems, 2019)

Improving conservation practice with principles and tools from systems thinking and evaluation - Andrew T. Knight; Carly N. Cook; Kent H. Redford; Duan Biggs; Claudia Romero; Alejandro Ortega-Argueta; Cameron D. Norman; Beverly Parsons; Martin Reynolds; Glenda Eoyang; Matt Keene (Sustainability Science, 2019)

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Conservation practitioners’ understanding of how to manage evolutionary processes - Carly N. Cook; Carla M. Sgrò (Conservation Biology, 2019)
Both academics and practitioners consider a lack of knowledge about evolutionary theory to be a general barrier to effectively managing genetic diversity. However, it is challenging to judge practitioners’ level of understanding and how this influences their management decisions. Knowledge built through experience may be difficult for practitioners to articulate, but could nonetheless result in appropriate management strategies. To date, researchers have assessed only the explicit (formal) knowledge practitioners have of evolutionary concepts. To explore practitioners’ understanding of evolutionary concepts, it is necessary to consider how they might apply explicit and implicit knowledge to their management decisions. Using an online survey, we asked Australian practitioners to respond to 2 common management scenarios in which there is strong evidence that managing genetic diversity can improve outcomes: managing small, isolated populations and sourcing seeds for restoration projects. In describing their approach to these scenarios, practitioners demonstrated a stronger understanding of the effective management of genetic diversity than the definitions of the relevant concepts. However, their management of genetic diversity within small populations was closer to best practice than for restoration projects. Moreover, the risks practitioners described in implementing best practice management were more likely to affect their approach to restoration than translocation projects. These findings provide evidence that strategies to build the capacity of practitioners to manage genetic diversity should focus on realistic management scenarios. Given that practitioners recognize the importance of adapting their practices and the strong evidence for the benefits of actively managing genetic diversity, there is hope that better engagement by evolutionary biologists with practitioners could facilitate significant shifts toward evolutionarily enlightened management.

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Population Pharmacokinetic Modeling in the Presence of Missing Time-Dependent Covariates: Impact of Body Weight on Pharmacokinetics of Paracetamol in Neonates - Wojciech Krzyzanski; Sarah F. Cook; Melanie Wilbaux; Catherine M. T. Sherwin; Karel Allegaert; An Vermeulen; John N. van den Anker (The AAPS Journal, 2019)

Cable bacteria promote DNRA through iron sulfide dissolution - Adam J. Kessler; Michaela Wawryk; Ugo Marzocchi; Keryn L. Roberts; Wei Wen Wong; Nils Risgaard‐Petersen; Filip J. R. Meysman; Ronnie N. Glud; Perran L. M. Cook (Limnology and Oceanography, 2019)
Cable bacteria represent a newly discovered group of filamentous microorganisms, which are capable of spatially separating the oxidative and reductive half‐reactions of their sulfide‐oxidizing metabolisms over centimeter distances. We investigated three ways that cable bacteria might interact with the nitrogen (N) cycle: (1) by reducing nitrate through denitrification or dissimilatory nitrate reduction to ammonium (DNRA) within their cathodic cells; (2) by nitrifying ammonium within their anodic cells; and (3) by indirectly affecting denitrification and/or DNRA by changing the Fe 2+ concentration in the surrounding sediment. We performed 15 N labeling laboratory experiments to measure these three processes using cable bacteria containing sediments from the Yarra River, Australia, and from Vilhelmsborg Sø, Denmark. Our results revealed that in the targeted systems, cable bacteria themselves did not perform significant rates of denitrification, DNRA, or nitrification. However, cable bacteria exhibited an important indirect effect, whereby they increased the Fe 2+ pool through iron sulfide dissolution. This elevated availability of Fe 2+ significantly increased DNRA and in some cases decreased denitrification. Thus, cable bacteria presence may affect the relative importance of DNRA in sediments and thus the extent by which bioavailable nitrogen is lost from the system.

Training Needs of Clinical and Research Professionals to Optimize Minority Recruitment and Retention in Cancer Clinical Trials - Soumya J. Niranjan; Raegan W. Durant; Jennifer A. Wenzel; Elise D. Cook; Mona N. Fouad; Selwyn M. Vickers; Badrinath R. Konety; Sarah B. Rutland; Zachary R. Simoni; Michelle Y. Martin (Journal of Cancer Education, 2019)

Using social‐network research to improve outcomes in natural resource management - Julie E. Groce; Megan A. Farrelly; Bradley S. Jorgensen; Carly N. Cook (Conservation Biology, 2019)
The conservation and management of natural resources operates in social–ecological systems in which resource users are embedded in social and environmental contexts that influence their management decisions. Characterizing social networks of resource users can be used to inform understanding of social influences on decision making, and social network analysis (SNA) has emerged as a useful technique to explore these relationships. We synthesized how SNA has been used in 85 studies of natural resource management. We considered how social networks and social processes (e.g., interactions between individuals) influence each other and in turn influence social outcomes (e.g., decisions or actions) that affect environmental outcomes (e.g., improved condition). Descriptive methods were used in 58% of the studies to characterize social processes, and 42% of the studies compared multiple networks or multiple points in time to assess social or environmental outcomes. In 4 studies, authors assessed network interventions intended to affect social processes or environmental outcomes. The heterogeneity in case studies, methods, and analyses preclude general lessons. Thus, to structure and further learning about the role of social networks in achieving environmental outcomes, we created a typology that deconstructs social processes, social outcomes, and environmental outcomes into themes and options of social and ecological measures within each. We suggest shifts in research foci toward intervention studies to aid in understanding causality and inform the design of conservation initiatives. There is a need to develop clearer justification and guidance around the proliferation of network measures. The use of SNA in natural resource management is expanding rapidly; thus, now is the time for the conservation community to build a more rigorous evidence base to demonstrate the extent to which social networks can play a role in achieving desired social and environmental outcomes.

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Persistence of Hepatitis A Virus in Fresh Produce and Production Environments, and the Effect of Disinfection Procedures: A Review - N. Cook; I. Bertrand; C. Gantzer; R. M. Pinto; A. Bosch (Food and Environmental Virology, 2018)

Using biological–physical modelling for informing sea lice dispersal in Loch Linnhe, Scotland - N K G Salama; A C Dale; V V Ivanov; P F Cook; C C Pert; C M Collins; B Rabe (Journal of Fish Diseases, 2018)
Sea lice are a constraint on the sustainable growth of Scottish marine salmonid aquaculture. As part of an integrated pest management approach, farms coordinate procedures within spatial units. We present observations of copepodids being at relatively greater density than nauplii in upper waters, which informs the development of surface layer sea lice transmission modelling of Loch Linnhe, Scotland, for informing farm parasite management. A hydrodynamic model is coupled with a biological particle‐tracking model, with characteristics of plankton sea lice. Simulations are undertaken for May and October 2011–2013, forced by local wind data collected for those periods. Particles are continually released from positions representing farm locations, weighted by relative farm counts, over a 2‐week period and tracked for a further 5 days. A comparison is made between modelled relative concentrations against physical and biological surveys to provide confidence in model outputs. Connectivity between farm locations is determined in order to propose potential coordination areas. Generally, connectivity depends on flow patterns in the loch and decreases with increased farm separation. The connectivity indices are used to estimate the origins of the sea lice population composition at each site, which may influence medicinal regimens to avoid loss of efficacy.

Optimizing a Knowledge-driven Prospectivity Model for Gold Deposits Within Peräpohja Belt, Northern Finland - V. Nykänen; T. Niiranen; F. Molnár; I. Lahti; K. Korhonen; N. Cook; P. Skyttä (Natural Resources Research, 2017)

Quantifying the extent of protected‐area downgrading, downsizing, and degazettement in Australia - Carly N. Cook; Rebecca S. Valkan; Michael B. Mascia; Melodie A. McGeoch (Conservation Biology, 2017)
The use of total area protected as the predominant indicator of progress in building protected area (PA) networks is receiving growing criticism. Documenting the full dynamics of PA networks, both in terms of the gains and losses in protection, provides a much more informative approach to tracking progress. To this end, documentation of PA downgrading, downsizing, and degazettement (PADDD) has increased. Studies of PADDD events generally fail to place these losses in the context of gains in protection; therefore, they omit important elements of PA network dynamics. To address this limitation, we used a spatially explicit approach to identify every parcel of land added to and excised from the Australian terrestrial PA network and PAs that had their level of protection changed over 17 years (1997–2014). By quantifying changes in the spatial configuration of the PA network with time‐series data (spatial layers for nine separate time steps), ours is the first assessment of the dynamics (increases and decreases in area and level of protection) of a PA network and the first comprehensive assessment of PADDD in a developed country. We found that the Australian network was highly dynamic; there were 5233 changes in area or level of protection over 17 years. Against a background of enormous increases in area protected, we identified over 1500 PADDD events, which affected over one‐third of the network, which were largely the result of widespread downgrading of protection. We believe our approach provides a mechanism for robust tracking of trends in the world's PAs through the use of data from the World Database on Protected Areas. However, this will require greater transparency and improved data standards in reporting changes to PAs.

Aligning science and policy to achieve evolutionarily enlightened conservation - Carly N. Cook; Carla M. Sgrò (Conservation Biology, 2017)
There is increasing recognition among conservation scientists that long‐term conservation outcomes could be improved through better integration of evolutionary theory into management practices. Despite concerns that the importance of key concepts emerging from evolutionary theory (i.e., evolutionary principles and processes) are not being recognized by managers, there has been little effort to determine the level of integration of evolutionary theory into conservation policy and practice. We assessed conservation policy at 3 scales (international, national, and provincial) on 3 continents to quantify the degree to which key evolutionary concepts, such as genetic diversity and gene flow, are being incorporated into conservation practice. We also evaluated the availability of clear guidance within the applied evolutionary biology literature as to how managers can change their management practices to achieve better conservation outcomes. Despite widespread recognition of the importance of maintaining genetic diversity, conservation policies provide little guidance about how this can be achieved in practice and other relevant evolutionary concepts, such as inbreeding depression, are mentioned rarely. In some cases the poor integration of evolutionary concepts into management reflects a lack of decision‐support tools in the literature. Where these tools are available, such as risk‐assessment frameworks, they are not being adopted by conservation policy makers, suggesting that the availability of a strong evidence base is not the only barrier to evolutionarily enlightened management. We believe there is a clear need for more engagement by evolutionary biologists with policy makers to develop practical guidelines that will help managers make changes to conservation practice. There is also an urgent need for more research to better understand the barriers to and opportunities for incorporating evolutionary theory into conservation practice.

Association of midlife smoking status with change in processing speed and mental flexibility among HIV-seropositive and HIV-seronegative older men: the Multicenter AIDS Cohort Study - Wajiha Z. Akhtar-Khaleel; Robert L. Cook; Steve Shoptaw; Eric N. Miller; Ned Sacktor; Pamela J. Surkan; Jim Becker; Linda A. Teplin; Rebecca J. Beyth; Catherine Price; Michael Plankey (Journal of NeuroVirology, 2017)

Virological Quality of Irrigation Water in Leafy Green Vegetables and Berry Fruits Production Chains - P. Kokkinos; I. Kozyra; S. Lazic; K. Söderberg; P. Vasickova; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; et al. (Food and Environmental Virology, 2017)

Environmental predictors of bovine Eimeria infection in western Kenya - D. N. Makau; G. K. Gitau; G. K. Muchemi; L. F. Thomas; E. A. J. Cook; N. A. Wardrop; E. M. Fèvre; W. A. de Glanville (Tropical Animal Health and Production, 2017)

Colistin combination therapy improves microbiologic cure in critically ill patients with multi-drug resistant gram-negative pneumonia - N. L. Parchem; K. A. Bauer; C. H. Cook; J. E. Mangino; C. D. Jones; K. Porter; C. V. Murphy (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Codivergence of the primary bacterial endosymbiont of psyllids versus host switches and replacement of their secondary bacterial endosymbionts - Aidan A. G. Hall; Jennifer L. Morrow; Caroline Fromont; Martin J. Steinbauer; Gary S. Taylor; Scott N. Johnson; James M. Cook; Markus Riegler (Environmental Microbiology, 2016)
Summary Coevolution between insects and bacterial endosymbionts contributes to the success of many insect lineages. For the first time, we tested for phylogenetic codivergence across multiple taxonomic scales, from within genera to superfamily between 36 psyllid species of seven recognised families (Hemiptera: Psylloidea), their exclusive primary endosymbiont Carsonella and more diverse secondary endosymbionts (S‐endosymbionts). Within Aphalaridae, we found that Carsonella and S‐endosymbionts were fixed in one Glycaspis and 12 Cardiaspina populations. The dominant S‐endosymbiont was Arsenophonus , while Sodalis was detected in one Cardiaspina species. We demonstrated vertical transmission for Carsonella and Arsenophonus in three Cardiaspina species. We found strong support for strict cospeciation and validated the informative content of Carsonella as extended host genome for inference of psyllid relationships. However, S‐endosymbiont and host phylogenies were incongruent, and displayed signs of host switching and endosymbiont replacement. The high incidence of Arsenophonus in psyllids and other plant sap‐feeding Hemiptera may be due to repeated host switching within this group. In two psyllid lineages, Arsenophonus and Sodalis genes exhibited accelerated evolutionary rates and AT‐biases characteristic of long‐term host associations. Together with strict vertical transmission and 100% prevalence within host populations, our results suggest an obligate, and not facultative, symbiosis between psyllids and some S‐endosymbionts.

Geochemistry and petrology of the indium-bearing polymetallic skarn ores at Pitkäranta, Ladoga Karelia, Russia - M. Valkama; K. Sundblad; N. J. Cook; V. I. Ivashchenko (Mineralium Deposita, 2016)

Flood risk management, an approach to managing cross-border hazards - L. J. Bracken; E. A. Oughton; A. Donaldson; B. Cook; J. Forrester; C. Spray; S. Cinderby; D. Passmore; N. Bissett (Natural Hazards, 2016)

Larvae influence thermoregulatory fanning behavior in honeybees (Apis mellifera L.) - C. N. Cook; S. Durzi; K. J. Scheckel; M. D. Breed (Insectes Sociaux, 2016)

Systems genetics of intravenous cocaine self-administration in the BXD recombinant inbred mouse panel - Price E. Dickson; Mellessa M. Miller; Michele A. Calton; Jason A. Bubier; Melloni N. Cook; Daniel Goldowitz; Elissa J. Chesler; Guy Mittleman (Psychopharmacology, 2016)

A bio-economic ‘war game’ model to simulate plant disease incursions and test response strategies at the landscape scale - David C. Cook; Jean-Philippe Aurambout; Oscar N. Villalta; Shuang Liu; Jacqueline Edwards; Savi Maharaj (Food Security, 2016)

Cardiorespiratory fitness is associated with brain structure, cognition, and mood in a middle-aged cohort at risk for Alzheimer’s disease - Elizabeth A. Boots; Stephanie A. Schultz; Jennifer M. Oh; Jordan Larson; Dorothy Edwards; Dane Cook; Rebecca L. Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; et al. (Brain Imaging and Behavior, 2015)

Using Strategic Foresight to Assess Conservation Opportunity - CARLY N. COOK; BONNIE C. WINTLE; STEPHEN C. ALDRICH; BRENDAN A. WINTLE (Conservation Biology, 2014)
The nature of conservation challenges can foster a reactive, rather than proactive approach to decision making. Failure to anticipate problems before they escalate results in the need for more costly and time‐consuming solutions. Proactive conservation requires forward‐looking approaches to decision making that consider possible futures without being overly constrained by the past. Strategic foresight provides a structured process for considering the most desirable future and for mapping the most efficient and effective approaches to promoting that future with tools that facilitate creative thinking. The process involves 6 steps: setting the scope, collecting inputs, analyzing signals, interpreting the information, determining how to act, and implementing the outcomes. Strategic foresight is ideal for seeking, recognizing, and realizing conservation opportunities because it explicitly encourages a broad‐minded, forward‐looking perspective on an issue. Despite its potential value, the foresight process is rarely used to address conservation issues, and previous attempts have generally failed to influence policy. We present the strategic foresight process as it can be used for proactive conservation planning, describing some of the key tools in the foresight tool kit and how they can be used to identify and exploit different types of conservation opportunities. Scanning is an important tool for collecting and organizing diverse streams of information and can be used to recognize new opportunities and those that could be created. Scenario planning explores how current trends, drivers of change, and key uncertainties might influence the future and can be used to identify barriers to opportunities. Backcasting is used to map out a path to a goal and can determine how to remove barriers to opportunities. We highlight how the foresight process was used to identify conservation opportunities during the development of a strategic plan to address climate change in New York State. The plan identified solutions that should be effective across a range of possible futures. Illustrating the application of strategic foresight to identify conservation opportunities should provide the impetus for decision makers to explore strategic foresight as a way to support more proactive conservation policy, planning, and management.

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Genetic diversity and complementary sex determination (CSD) in Dolerus aeneus (Hymenoptera, Symphyta): implications for the conservation of an ecologically-important sawfly - N. Cook; S. F. Hubbard; A. J. Karley; J. R. Russell (Conservation Genetics, 2013)

Contribution of Systematic Reviews to Management Decisions - CARLY N. COOK; HUGH P. POSSINGHAM; RICHARD A. FULLER (Conservation Biology, 2013)
Systematic reviews comprehensively summarize evidence about the effectiveness of conservation interventions. We investigated the contribution to management decisions made by this growing body of literature. We identified 43 systematic reviews of conservation evidence, 23 of which drew some concrete conclusions relevant to management. Most reviews addressed conservation interventions relevant to policy decisions; only 35% considered practical on‐the‐ground management interventions. The majority of reviews covered only a small fraction of the geographic and taxonomic breadth they aimed to address (median = 13% of relevant countries and 16% of relevant taxa). The likelihood that reviews contained at least some implications for management tended to increase as geographic coverage increased and to decline as taxonomic breadth increased. These results suggest the breadth of a systematic review requires careful consideration. Reviews identified a mean of 312 relevant primary studies but excluded 88% of these because of deficiencies in design or a failure to meet other inclusion criteria. Reviews summarized on average 284 data sets and 112 years of research activity, yet the likelihood that their results had at least some implications for management did not increase as the amount of primary research summarized increased. In some cases, conclusions were elusive despite the inclusion of hundreds of data sets and years of cumulative research activity. Systematic reviews are an important part of the conservation decision making tool kit, although we believe the benefits of systematic reviews could be significantly enhanced by increasing the number of reviews focused on questions of direct relevance to on‐the‐ground managers; defining a more focused geographic and taxonomic breadth that better reflects available data; including a broader range of evidence types; and appraising the cost‐effectiveness of interventions. Contribuciones de las Revisiones Sistemáticas a las Decisiones de Manejo

Molecular Characterization of Mutant Mouse Strains Generated from the EUCOMM/KOMP-CSD ES Cell Resource - Edward Ryder; Diane Gleeson; Debarati Sethi; Sapna Vyas; Evelina Miklejewska; Priya Dalvi; Bishoy Habib; Ross Cook; Matthew Hardy; Kalpesh Jhaveri; Joanna Bottomley; Hannah Wardle-Jones; et al. (Mammalian Genome, 2013)

Achieving Conservation Science that Bridges the Knowledge–Action Boundary - CARLY N. COOK; MICHAEL B. MASCIA; MARK W. SCHWARTZ; HUGH P. POSSINGHAM; RICHARD A. FULLER (Conservation Biology, 2013)
There are many barriers to using science to inform conservation policy and practice. Conservation scientists wishing to produce management‐relevant science must balance this goal with the imperative of demonstrating novelty and rigor in their science. Decision makers seeking to make evidence‐based decisions must balance a desire for knowledge with the need to act despite uncertainty. Generating science that will effectively inform management decisions requires that the production of information (the components of knowledge) be salient (relevant and timely), credible (authoritative, believable, and trusted), and legitimate (developed via a process that considers the values and perspectives of all relevant actors) in the eyes of both researchers and decision makers. We perceive 3 key challenges for those hoping to generate conservation science that achieves all 3 of these information characteristics. First, scientific and management audiences can have contrasting perceptions about the salience of research. Second, the pursuit of scientific credibility can come at the cost of salience and legitimacy in the eyes of decision makers, and, third, different actors can have conflicting views about what constitutes legitimate information. We highlight 4 institutional frameworks that can facilitate science that will inform management: boundary organizations (environmental organizations that span the boundary between science and management), research scientists embedded in resource management agencies, formal links between decision makers and scientists at research‐focused institutions, and training programs for conservation professionals. Although these are not the only approaches to generating boundary‐spanning science, nor are they mutually exclusive, they provide mechanisms for promoting communication, translation, and mediation across the knowledge–action boundary. We believe that despite the challenges, conservation science should strive to be a boundary science, which both advances scientific understanding and contributes to decision making. Logrando que la Ciencia de la Conservación Trasponga la Frontera Conocimiento‐Acción

Harmonised Investigation of the Occurrence of Human Enteric Viruses in the Leafy Green Vegetable Supply Chain in Three European Countries - P. Kokkinos; I. Kozyra; S. Lazic; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; M. D’Agostino; N. Cook; et al. (Food and Environmental Virology, 2012)

An intra-specific consensus genetic map of pigeonpea [Cajanus cajan (L.) Millspaugh] derived from six mapping populations - Abhishek Bohra; Rachit K. Saxena; B. N. Gnanesh; Kulbhushan Saxena; M. Byregowda; Abhishek Rathore; P. B. KaviKishor; Douglas R. Cook; Rajeev K. Varshney (Theoretical and Applied Genetics, 2012)

Quantifying denitrification in rippled permeable sands through combined flume experiments and modeling - Adam J. Kessler; Ronnie N. Glud; M. Bayani Cardenas; Morten Larsen; Michael F. Bourke; Perran L. M. Cook (Limnology and Oceanography, 2012)
We measured denitrification in permeable sediments in a sealed flume tank with environmentally representative fluid flow and solute transport behavior using novel measurements. Numerical flow and reactive transport models representing the flume experiments were implemented to provide mechanistic insight into the coupled hydrodynamic and biogeochemical processes. There was broad agreement between the model results and experimental data. The model showed that the coupling between nitrification and denitrification was relatively weak in comparison to that in cohesive sediments. This was due to the direct advective transport between anoxic pore water and the overlying water column, and little interaction between the mostly oxic advective region and the underlying anoxic region. Denitrification was therefore mainly fueled by nitrate supplied from the water column. This suggests that the capacity of permeable sediments with nonmigratory ripples to remove bioavailable nitrogen from coastal ecosystems is lower than that of cohesive sediments. We conclude that while experimental measurements provide a good starting point for constraining key parameters, reactive transport models with realistic kinetic and transport parameters provide critical insight into biogeochemical processes in permeable sediment that are difficult to experimentally evaluate.

Taxonomy and species boundaries in the coral genus Favia Milne Edwards and Haime, 1857 (Cnidaria: Scleractinia) from Thailand revealed by morphological and genetic data - N. Kongjandtre; T. Ridgway; L. G. Cook; T. Huelsken; A. F. Budd; O. Hoegh-Guldberg (Coral Reefs, 2012)

Reconciling estimates of the contemporary North American carbon balance among terrestrial biosphere models, atmospheric inversions, and a new approach for estimating net ecosystem exchange from inventory‐based data - Daniel J. Hayes; David P. Turner; Graham Stinson; A. David McGuire; Yaxing Wei; Tristram O. West; Linda S. Heath; Bernardus de Jong; Brian G. McConkey; Richard A. Birdsey; Werner A. Kurz; Andrew R. Jacobson; et al. (Global Change Biology, 2012)
We develop an approach for estimating net ecosystem exchange ( NEE ) using inventory‐based information over North America ( NA ) for a recent 7‐year period (ca. 2000–2006). The approach notably retains information on the spatial distribution of NEE , or the vertical exchange between land and atmosphere of all non‐fossil fuel sources and sinks of CO 2 , while accounting for lateral transfers of forest and crop products as well as their eventual emissions. The total NEE estimate of a −327 ± 252 TgC yr −1 sink for NA was driven primarily by CO 2 uptake in the Forest Lands sector (−248 TgC yr −1 ), largely in the Northwest and Southeast regions of the US, and in the Crop Lands sector (−297 TgC yr −1 ), predominantly in the Midwest US states. These sinks are counteracted by the carbon source estimated for the Other Lands sector (+218 TgC yr −1 ), where much of the forest and crop products are assumed to be returned to the atmosphere (through livestock and human consumption). The ecosystems of Mexico are estimated to be a small net source (+18 TgC yr −1 ) due to land use change between 1993 and 2002. We compare these inventory‐based estimates with results from a suite of terrestrial biosphere and atmospheric inversion models, where the mean continental‐scale NEE estimate for each ensemble is −511 TgC yr −1 and −931 TgC yr −1 , respectively. In the modeling approaches, all sectors, including Other Lands, were generally estimated to be a carbon sink, driven in part by assumed CO 2 fertilization and/or lack of consideration of carbon sources from disturbances and product emissions. Additional fluxes not measured by the inventories, although highly uncertain, could add an additional −239 TgC yr −1 to the inventory‐based NA sink estimate, thus suggesting some convergence with the modeling approaches.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Escherichia coli Diversity in Livestock Manures and Agriculturally Impacted Stream Waters - Kimberly L. Cook; Carl H. Bolster; Kati A. Ayers; Dale N. Reynolds (Current Microbiology, 2011)

Transcriptome sequencing of an ecologically important graminivorous sawfly: a resource for marker development - N. Cook; N. Aziz; P. E. Hedley; J. Morris; L. Milne; A. J. Karley; S. F. Hubbard; J. R. Russell (Conservation Genetics Resources, 2011)

Factors limiting the health of semi-scavenging ducks in Bangladesh - M. A. Hoque; L. F. Skerratt; A. J. C. Cook; S. A. Khan; D. Grace; M. R. Alam; A. Vidal-Diez; N. C. Debnath (Tropical Animal Health and Production, 2011)

Population structure and linkage disequilibrium in oat (Avena sativa L.): implications for genome-wide association studies - M. A. Newell; D. Cook; N. A. Tinker; J.-L. Jannink (Theoretical and Applied Genetics, 2011)

Integration of novel SSR and gene-based SNP marker loci in the chickpea genetic map and establishment of new anchor points with Medicago truncatula genome - Spurthi N. Nayak; Hongyan Zhu; Nicy Varghese; Subhojit Datta; Hong-Kyu Choi; Ralf Horres; Ruth Jüngling; Jagbir Singh; P. B. Kavi Kishor; S. Sivaramakrishnan; Dave A. Hoisington; Günter Kahl; et al. (Theoretical and Applied Genetics, 2010)

A mark-recapture population estimate for invasive silver carp (Hypophthalmichthys molitrix) in the La Grange Reach, Illinois River - Greg G. Sass; Thad R. Cook; Kevin S. Irons; Michael A. McClelland; Nerissa N. Michaels; T. Matthew O’Hara; Matthew R. Stroub (Biological Invasions, 2010)

Reconstructing ENSO: the influence of method, proxy data, climate forcing and teleconnections - Rob Wilson; Edward Cook; Rosanne D'Arrigo; Nadja Riedwyl; Michael N. Evans; Alexander Tudhope; Rob Allan (Journal of Quaternary Science, 2010)
In this study we compare three newly developed independent NINO3.4 sea surface temperature (SST) reconstructions using data from (1) the central Pacific (corals), (2) the TexMex region of the USA (tree rings) and (3) other regions in the Tropics (corals and an ice core) which are teleconnected with central Pacific SSTs in the 20th century. Although these three reconstructions are strongly calibrated and well verified, inter‐proxy comparison shows a significant weakening in inter‐proxy coherence in the 19th century. This breakdown in common signal could be related to insufficient data, dating errors in some of the proxy records or a breakdown in El Niño–Southern Oscillation's (ENSO's) influence on other regions. However, spectral analysis indicates that each reconstruction portrays ENSO‐like spectral properties. Superposed epoch analysis also shows that each reconstruction shows a generally consistent ‘El Niño‐like’ response to major volcanic events in the following year, while during years T + 4 to T + 7 ‘La Niña‐like’ conditions prevail. These results suggest that each of the series expresses ENSO‐like ‘behaviour’, but this ‘behaviour’ does not appear to be spatially or temporally consistent. This result may reflect published observations that there appear to be distinct ‘types’ of ENSO variability depending on location within the tropical Pacific. Future work must address potential dating issues within some proxies (i.e. sampling of multiple coral heads for one location) as well as assessing the time stability of local climate relationships with central Pacific SSTs. More emphasis is needed on sampling new and extending old coral proxy records from the crucial central and eastern tropical Pacific region. Copyright © 2009 John Wiley & Sons, Ltd. and © Crown Copyright 2009.

Seizure Detection Using Seizure Probability Estimation: Comparison of Features Used to Detect Seizures - Levin Kuhlmann; Anthony N. Burkitt; Mark J. Cook; Karen Fuller; David B. Grayden; Linda Seiderer; Iven M. Y. Mareels (Annals of Biomedical Engineering, 2009)

Accountability, Reporting, or Management Improvement? Development of a State of the Parks Assessment System in New South Wales, Australia - Marc Hockings; Carly N. Cook; R. W. Carter; Robyn James (Environmental Management, 2009)

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Another look at nagyágite from the type locality, S $\check{\rm{a}}$ c $\check{\rm{a}}$ rîmb, Romania: Replacement, chemical variation and petrogenetic implications - C. L. Ciobanu; N. J. Cook; A. Pring; G. Damian; N. Căpraru (Mineralogy and Petrology, 2008)

Summary Workshop Report: Bioequivalence, Biopharmaceutics Classification System, and Beyond - James E. Polli; Bertil S. I. Abrahamsson; Lawrence X. Yu; Gordon L. Amidon; John M. Baldoni; Jack A. Cook; Paul Fackler; Kerry Hartauer; Gordon Johnston; Steve L. Krill; Robert A. Lipper; Waseem A. Malick; et al. (The AAPS Journal, 2008)

Brian MacMahon (1923–2007): founder of modern epidemiology - D. Trichopoulos; P. Cole; E. F. Cook; M. Feinleib; R. Hoover; C.-C. Hsieh; D. Hunter; R. Monson; N. Mueller; M. Rahu; E. Rimm; K. Rothman; et al. (Cancer Causes & Control, 2008)

Andropogon gayanus (Gamba Grass) Invasion Increases Fire-mediated Nitrogen Losses in the Tropical Savannas of Northern Australia - N. A. Rossiter-Rachor; S. A. Setterfield; M. M. Douglas; L. B. Hutley; G. D. Cook (Ecosystems, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Tellurides from Sunrise Dam gold deposit, Yilgarn Craton, Western Australia: a new occurrence of nagyágite - Y.-H. Sung; C. L. Ciobanu; A. Pring; J. Brügger; W. Skinner; N. J. Cook; M. Nugus (Mineralogy and Petrology, 2007)

Neurobehavioral mutants identified in an ENU-mutagenesis project - Melloni N. Cook; Jonathan P. Dunning; Ronald G. Wiley; Elissa J. Chesler; Dabney K. Johnson; Darla R. Miller; Dan Goldowitz (Mammalian Genome, 2007)

Benthic solute exchange and carbon mineralization in two shallow subtidal sandy sediments: Effect of advective pore‐water exchange - Perran L. M. Cook; Frank Wenzhöfer; Ronnie N. Glud; Felix Janssen; Markus Huettel (Limnology and Oceanography, 2007)
We conducted four field campaigns to evaluate benthic O 2 consumption and the effect of advective pore‐water flow in nearshore permeable sediments in the North Sea and Baltic Sea. Advective pore‐water transport had a marked effect on the benthic exchange of O 2 and TCO 2 in benthic chamber incubations, with the rates of exchange increasing by a factor of up to 2.5 when imposing flushing rates of 100‐300 L m −2 d −1 , compared to settings with diffusive exchange only. Estimates of in situ exchange rates using oxygen penetration and volumetric O 2 consumption and TCO 2 production rates were within the range measured in the chambers. The contribution of advection to solute exchange was highly variable and dependent on sediment topography. Advective processes also had a pronounced influence on the in situ distribution of O 2 within the sediment, with characteristic two‐dimensional patterns of O 2 distribution across ripples, and also deep subsurface O 2 pools, being observed. Mineralization pathways were predominantly aerobic when benthic mineralization rates were low and advective pore‐water flow high as a result of well‐developed sediment topography. By contrast, mineralization proceeded predominantly through sulfate reduction when benthic mineralization rates were high and advective pore‐water flow low as a result of poorly developed topography. Previous studies of benthic mineralization in shallow sandy sediments have generally ignored these dynamics and, hence, have overlooked crucial aspects of permeable sediment function in coastal ecosystems.

Isolation of viral haemorrhagic septicaemia virus from mummichog, stickleback, striped bass and brown trout in eastern Canada - N Gagné; A‐M MacKinnon; L Boston; B Souter; M Cook‐Versloot; S Griffiths; G Olivier (Journal of Fish Diseases, 2007)
Viral haemorrhagic septicaemia virus (VHSV) was isolated from mortalities occurring in populations of mummichog, Fundulus heteroclitus , stickleback, Gasterosteus aculeatus aculeatus , brown trout, Salmo trutta , and striped bass, Morone saxatilis , in New Brunswick and Nova Scotia, Canada. The isolated viral strains produced a cytopathic effect on the epithelioma papillosum cyprini cell line. Serum neutralization indicated the virus was VHSV and sequencing identified the rhabdovirus isolates as the North American strain of VHSV. Phylogenetic analysis indicated that the isolates are closely related and form a distinguishable subgroup of North American type VHSV. To our knowledge, this is the first report of VHSV in mummichog and striped bass.

Behavioural and chemical ecology underlying the success of turnip rape (Brassica rapa) trap crops in protecting oilseed rape (Brassica napus) from the pollen beetle (Meligethes aeneus) - S. M. Cook; H. B. Rasmussen; M. A. Birkett; D. A. Murray; B. J. Pye; N. P. Watts; I. H. Williams (Arthropod-Plant Interactions, 2007)

Allelic and haplotypic diversity at the major histocompatibility class II within domesticated Australian Atlantic salmon ( Salmo salar L.) - J. W. Wynne; M. T. Cook; B. H. Holmes; N. G. Elliott (Journal of Fish Biology, 2007)
Variation within the major histocompatibility (MH) class II alpha gene ( Sasa‐DAA ) was compared between domesticated Australian Atlantic salmon and their ancestral Canadian population. The level of Sasa‐DAA and MH class II beta gene ( Sasa‐DAB ) sequence variation was also examined within the Australian population and compared with that published for European Atlantic salmon populations. In contrast to variation previously reported for non‐coding microsatellite loci, a high level of MH class II allelic variation has been maintained within the domesticated Australian populations. Furthermore, a high level of Sasa‐DAA and Sasa‐DAB allele sequence diversity was also observed and exceeded that reported for other cultured Atlantic salmon populations. The number of Sasa‐DAB allele sequences (14) surpassed the number of Sasa‐DAA allele sequences (9) to produce 14 unique class II haplotypes. We conclude that the Australian Atlantic salmon populations show high MH class II allelic and haplotypic variation compared with both its ancestral Canadian population and other cultured Atlantic salmon populations.

Enhanced sucrose pellet consumption induced by benzodiazepine-type drugs in squirrel monkeys: role of GABAA receptor subtypes - Angela N. Duke; Donna M. Platt; James M. Cook; Shengming Huang; Wenyuan Yin; Bruce A. Mattingly; James K. Rowlett (Psychopharmacology, 2006)

Preface – Special Issue: Telluride and selenide minerals in gold deposits – how and why? - C. L. Ciobanu; N. J. Cook; P. G. Spry (Mineralogy and Petrology, 2006)

Gold scavenged by bismuth melts: An example from Alpine shear-remobilizates in the Highiş Massif, Romania - C. L. Ciobanu; N. J. Cook; F. Damian; G. Damian (Mineralogy and Petrology, 2006)

Geographic variation in patterns of nestedness among local stream fish assemblages in Virginia - Rosamonde R. Cook; Paul L. Angermeier; Debra S. Finn; N. LeRoy Poff; Kirk L. Krueger (Oecologia, 2004)

A Modeling System for Studying Climate Controls on Mountain Glaciers with Application to the Patagonian Icefields - Kerry H. Cook; Xiaosong Yang; Corinne M. Carter; Brian N. Belcher (Climatic Change, 2003)

An Integrated Pharmacodynamic Analysis of Erythropoietin, Reticulocyte, and Hemoglobin Responses in Acute Anemia - P. Veng-Pederson; S. Chapel; P. R. L. Schmidt; N. H. Al-Huniti; R. T. Cook; J. A. Widness (Pharmaceutical Research, 2002)

Molecular analysis of the genotype-phenotype relationship in factor VII deficiency - D. Millar; G. Kemball-Cook; J. McVey; E. Tuddenham; A. Mumford; G. Attock; J. Reverter; N. Lanir; L. Parapia; J. Reynaud; E. Meili; A. von Felton; et al. (Human Genetics, 2000)

Oxide-sulphide relationships in sodalite-bearing metasomatites of the Epembe-Swartbooisdrif Alkaline Province, north-west Namibia - V. von Seckendorff; K. Drüppel; M. Okrusch; N. J. Cook; S. Littmann (Mineralium Deposita, 2000)

Late-Variscan antimony mineralisation in the Rheinisches Schiefergebirge, NW Germany: evidence for stibnite precipitation by drastic cooling of high-temperature fluid systems - T. Wagner; N. J. Cook (Mineralium Deposita, 2000)

Mineralogy and textural relationships among sulphosalts and related minerals in the Bleikvassli Zn-Pb-(Cu) deposit, Nordland, Norway - N. J. Cook; P. G. Spry; F. M. Vokes (Mineralium Deposita, 1998)

Thermobarometry of the Bleikvassli Zn-Pb-(Cu) deposit, Nordland, Norway - J. L. Rosenberg; P. G. Spry; C. E. Jacobson; N. J. Cook; F. M. Vokes (Mineralium Deposita, 1998)

The effect of severe eccentric exercise-induced muscle damage on plasma elastase, glutamine and zinc concentrations - M. Gleeson; N. P. Walsh; A. K. Blannin; P. J. Robson; L. Cook; A. E. Donnelly; S. H. Day (European Journal of Applied Physiology, 1998)

The effects of high-intensity intermittent exercise on the plasma concentrations of glutamine and organic acids - N. P. Walsh; A. K. Blannin; A. M. Clark; L. Cook; P. J. Robson; M. Gleeson (European Journal of Applied Physiology, 1998)

Linkage mapping of α3, α5, and β4 neuronal nicotinic acetylcholine receptors to rat Chromosome 8 - Melloni N. Cook; André Ramos; Hélène Courvoisier; Marie-Pierre Moisan (Mammalian Genome, 1998)

Sphalerite remobilization during multistage hydrothermal mineralization events ?examples from siderite-Pb-Zn-Cu-Sb veins, Rheinisches Schiefergebirge, Germany - T. Wagner; N. J. Cook (Mineralogy and Petrology, 1998)

Homology modelling of the catalytic domain of early mammalian protein C: evolution of structural features - A. I. Wacey; M. Krawczak; G. Kemball-Cook; D. N. Cooper (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Complementation with an avian influenza virus is required for synthesis of M protein of a human strain in chicken erythrocytes - R. F. Cook; R. J. Avery; N. J. Dimmock (Archives of Virology, 1980)

On the uniqueness of the flagellum ofThiobacillus thiooxidans - R. N. Doetsch; T. M. Cook; Z. Vaituzis (Antonie van Leeuwenhoek, 1967)

Sectional notes - W. B. Ward; Allan Purdy; Marx Koeiinke; H. J. Evans; Harrold Mattson; E. B. Tussing; Harold T. Cook; M. R. Harris; R. E. Goodwin; W. N. Keenan (American Journal of Potato Research, 1947)